Titulação de anticorpos anti-Pseudomas aeruginosa, na população hospitalar e não hospitalar, em Portugal - Ferreira, Maria Odette Santos (2017)
We describe a new techniquc of agglutination using ons 80-wells plaques for titration of antí-Pseudomonas aeruginosa antibodies using a bacterial antigene stained by 2, 3, 5 triphenyltetrazolium chloride and inoctivated by sodium merthiolate. This antigene was prepared from the 10 serotypes most frequently observed in Portugal. The technique was used in our research work and titration of seric antibodies present in 1310 human serums of from various origins (infected people in hospitais, healthy people, adults, childrens, etc... of Lisboa and four other places in the same region). The resultas obtained were comparede with those described in France and other countries.